2021
DOI: 10.3390/ijms222212403
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis: A Double-Edged Sword in Gastrointestinal Disease

Abstract: Ferroptosis is a novel form of regulated cell death (RCD) that is typically accompanied by iron accumulation and lipid peroxidation. In contrast to apoptosis, autophagy, and necroptosis, ferroptosis has unique biological processes and pathophysiological characteristics. Since it was first proposed in 2012, ferroptosis has attracted attention worldwide. Ferroptosis is involved in the progression of multiple diseases and could be a novel therapeutic target in the future. Recently, tremendous progress has been ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 140 publications
(164 reference statements)
2
31
0
Order By: Relevance
“…Polyunsaturated fatty acids (PUFAs), especially arachidonic acid (AA) and linoleic acid, preserve highly oxidizable methylene groups that bridge two double bonds and are the two major substrates for lipid peroxidation (66,95). Compared to the less reactive monounsaturated and saturated fatty acids, PUFAs are ideal targets for attack by ROS, and accumulated cytosolic and lipid ROS serve as potent triggers to oxidize PUFAs to generate lipid peroxides, thus inducing ferroptosis (10,96). The oxidation of PUFAs can be regulated by either an enzymatic reaction, such as a lipoxygenase-mediated reaction, or a nonenzymatic reaction, such as a Fenton-type reaction, in the plasma membrane (57,97).…”
Section: Ferroptosis and Inflammatory Bowel Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyunsaturated fatty acids (PUFAs), especially arachidonic acid (AA) and linoleic acid, preserve highly oxidizable methylene groups that bridge two double bonds and are the two major substrates for lipid peroxidation (66,95). Compared to the less reactive monounsaturated and saturated fatty acids, PUFAs are ideal targets for attack by ROS, and accumulated cytosolic and lipid ROS serve as potent triggers to oxidize PUFAs to generate lipid peroxides, thus inducing ferroptosis (10,96). The oxidation of PUFAs can be regulated by either an enzymatic reaction, such as a lipoxygenase-mediated reaction, or a nonenzymatic reaction, such as a Fenton-type reaction, in the plasma membrane (57,97).…”
Section: Ferroptosis and Inflammatory Bowel Diseasesmentioning
confidence: 99%
“…The studies thus provide strong evidence that an irondependent accumulation of ROS contributes to ferroptosis. Following these early studies, subsequent works revealed that ferroptosis occurs in many clinical disorders, such as kidney disease, cardiomyopathy, atherosclerosis, neurodegenerative disorders, ischemia/reperfusion (I/R) injury, cancers and immune-mediated diseases, such as diabetes, multiple sclerosis, and asthma (9,10). In comparison, given that most of the published studies have focused on investigating the roles of ferroptosis in cancer (11), knowledge about the involvement and mechanisms of ferroptosis in autoimmune diseases remains largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Free PUFAs cannot induce ferroptosis. After incorporation into membrane lipids, including phospholipids (PLs), the excessive accumulation of oxidized (PUFA-PLs) can contribute to ferroptosis ( Xu et al, 2021 ). Lysophosphatidylcholine acyltransferase 3 and acyl-coenzyme A synthetase long-chain family member 4 (ACSL4) are involved in activating and incorporating PUFAs into PLs ( Brown et al, 2019 ).…”
Section: Mechanisms Underlying Ferroptosismentioning
confidence: 99%
“…Ferroptosis is a form of cell death that differs from apoptosis and pyroptosis, The usual causes are lipid peroxidation, iron accumulation, and cell membrane breakdown. 8 .Some other research had found that ferroptosis can be participant in the regulation of in ammatory bowel disease 9 . Huang et.al indicated that ferroptosis-related hub gene STAT3(signal transducer and activator of transcription 3) mediated the ferroptosis process and promoted ulcerative colitis occured 10 .…”
Section: Introductionmentioning
confidence: 98%